Ethno pharmacological Efficiency of Andrographis Paniculata against Tuber Rot Disease of Manihot Esculenta (Cassava): Life Sciences-Agriculture for Better Food - Palani Ruba; Edward Gnanaraj Wesely; Albert Hannah Selvakumari; Michael Helan Soundra Rani (International Journal of Life Science and Pharma Research, 2022)
Cassava is a chief and energy rich carbohydrates food, which might be the reason many parasitic fungi adhere within the plant that causes huge damage to the crop during the post harvesting stage or storage period. In the present study, the ethno-based possible eradication of parasitic fungi was highlighted. Andrographis paniculata Burm. f. Nees and Stachytarpheta indica were chosen for its popular medicinal values and the phytochemical contents were characterized. Its potency showed an inhibitory effects against tuber rot disease causing fungal pathogens viz., Rhizopus sp, Mucor sp., Aspergillus niger, Aspergillus flavus and Fusarium oxysporum in Cassava by disc – diffusion methods. The diameter of the zone of inhibition at various concentrations (2.5, 5, 7.5 and 10 w/v) of leaf extracts was observed with the maximum in A. paniculata (20mm with 10 w/v conc.) against Fusarium oxysporum followed by A. niger (17mm at 10w/v conc.). The preliminary phytochemical screening of Andrographis paniculata revealed the presence of phytoconstituents like alkaloids, flavonoids, phenols, and tannins. In GCMS analysis, Benzene,1,2,3-trimethoxy-5-(2-propenyl)-, Cyclopenta [c] pyran-4-carboxylic acid, 7-methyl-, methyl ester and 9,12,15- Octadecatrienoic acid, methyl ester, (Z, Z, Z)- covered the high areas, that might be responsible or can possess the antifungal activity against Tuber root rot causing fungal pathogens. Furthermore, extensive studies are recommended to characterize each compound in the crude extracts of A. paniculata to enhance or to acclaim remedy for various diseases in plants. This study reveals the acknowledgement of the medicinal plant A. paniculata for its remarkable organic or eco-friendly fungicide potential against cassava tuber rot diseases.